Sequential Changes in Circulating Tumor Cells in the Peripheral Blood of Pancreatic Cancer Patients with Preoperative Chemotherapy Using a New Immunocytology-Based, Light Microscopic CTC Detection Platform - Kohei Yasui; Takuya Saito; Sho Ueda; Kentaro Shinohara; Yasuyuki Fukami; Tsuyoshi Sano; Hayao Nakanishi (Diagnostics)
Background: Circulating tumor cells (CTCs) have recently been developed as biomarkers. Several studies have reported on the clinical use of CTCs to assess drug resistance in various cancers. However, sequential and multiple CTC measurements during chemotherapy are relatively rare. We recently reported a transient increase in CTCs early after chemotherapy by sequentially detecting CTCs in a human pancreatic cancer xenograft model in nude mice. Method: In the present study, using a newly developed immunocytology and glass slide-based convenient CTC detection platform, we examined CTC numbers sequentially before, during, and after chemotherapy in the peripheral blood of 14 pancreatic cancer patients, pathological stage (pStage) I-IV, who underwent surgery with preoperative chemotherapy and GS (Gem/S-1) and GnP (Gem/nab-PTX). Results: Among patients with strongly or weakly elevated CTC counts (3–44/5 mL of blood) following GS treatment, four out of six pancreatic cancer patients were judged to have a partial response (PR), and two out of six were deemed to have stable disease (SD) as a clinical response based on the CT image. In contrast, in patients with GnP therapy, three out of four patients showed no CTC response, and these three patients were judged to have progressive disease (PD), while the remaining one patient was judged to have SD in terms of their clinical response. Conclusion: These results suggest that sequential CTC monitoring during preoperative chemotherapy in pancreatic cancer patients can be a helpful liquid biopsy diagnostic tool as a therapeutic marker to predict tumor chemosensitivity and chemoresistance in clinical settings. Further large-scale clinical studies are required to confirm and clarify this hypothesis.